2009
DOI: 10.1007/s10620-009-0795-3
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound of Hepatic and System Hemodynamics in Patients with Alcoholic Liver Cirrhosis

Abstract: This article was published with the given name and family name for each of the eight authors in reverse order. The correct order, given name followed by family name, is shown in this erratum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…We found that the HARI did not significantly correlate with MELD scores, splenomegaly, or ascites. This is concordant with several previous investigations of the HARI in the setting of cirrhosis, which yielded variable results . Most of these previous studies did not measure the HAv; rather, they focused on the HARI, perhaps because of the fact that the resistive index is easier to measure than the HAv, which requires angle correction for accurate measurement.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the HARI did not significantly correlate with MELD scores, splenomegaly, or ascites. This is concordant with several previous investigations of the HARI in the setting of cirrhosis, which yielded variable results . Most of these previous studies did not measure the HAv; rather, they focused on the HARI, perhaps because of the fact that the resistive index is easier to measure than the HAv, which requires angle correction for accurate measurement.…”
Section: Discussionsupporting
confidence: 89%
“…The oxidation of plasma albumin in these patients was more extensive and severe ( Table 2) and may be one of the important pathological conditions responsible for systemic complications in SAH. (35,36) The results of our study demonstrate that oxidative damage of circulating albumin in SAH destroys the homeostatic balance between plasma antioxidant and prooxidant properties, potentially generating a vicious circle of progressive systemic oxidative stress.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast to previous studies that were based on quantitative flow measurements (7,15,16,35), we evaluated not just portal venous hemodynamics but the flow in the extrahepatic vessels as well, including the superior mesenteric and splenic veins and intrahepatic vessels with the right and left intrahepatic portal vein branches. Almost all extrahepatic vessels were well visualized with good quality, with some limitations in the left intrahepatic branches.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in US studies have demonstrated a significant correlation between main portal vein flow volume and mean velocity and the liver cirrhosis stage (6,7). Nevertheless, the diagnostic value of Doppler US is limited, as a result of interobserver dependency and variability in the actual portal blood flow velocity values caused by measurement errors or poor examination conditions when taking Doppler measurements.…”
Section: Gastrointestinal Imaging: Three-dimensional Portal Venous Hementioning
confidence: 99%